Protecting the North Sea: Aberdeenshire - Conlon, Suzanne; Perry, Allison L.; García, Silvia; Blanco, Jorge; Álvarez, Helena; Aguilar, Ricardo; Oceana (Zenodo, 2020)
The sea surrounding Aberdeenshire is home to a rich diversity of seabed ecosystems, ranging from kelp forests along the coast to burrowed mud within the Southern Trench, a deep seabed incision that is both geologically and ecologically important. The value of the Southern Trench as a biodiversity hotspot has been recognised by the Scottish government, which proposed the creation of the Southern Trench Nature Conservation Marine Protected Area (NCMPA) to protect four biodiversity features (burrowed mud, fronts, minke whale, and shelf deeps) and two geodiversity features (Quaternary of Scotland and submarine mass movement). However, it is not yet known whether the site will in fact be designated, and other protection of benthic ecosystems in the Aberdeenshire area remains limited. In 2017, Oceana carried out a research expedition in the waters of Aberdeenshire, to gather further information about the area’s benthic species and communities. Surveys were conducted mainly through low-impact visual means (filming via a remotely operated vehicle and by professional divers) and were complemented with seabed grab sampling of infauna. Both protected and unprotected locations were surveyed, including points within the area’s three existing marine protected areas (none of which protect seabed ecosystems) and the proposed Southern Trench NCMPA. In total, Oceana documented 481 taxa (351 to the species level), in association with 14 habitat types. Among the marine features recorded were 16 species and seven habitat types that are considered priorities for conservation under Scottish or international frameworks. Key findings included reefs and other aggregations formed by ross worm ( Sabellaria spinulosa ), kelp forests, submerged caves, and sea pen and burrowing megafauna communities. On the basis of its findings, Oceana strongly supports the designation of the Southern Trench NCMPA, and encourages the Scottish government to grant formal protection to other features found within the site. In particular, the Aberdeenshire area appears to be important for ross worm ( S. spinulosa ) reefs, both within the proposed Southern Trench site and beyond its southern boundary. Oceana urges the Scottish authorities to extend the site boundaries to encompass these vulnerable habitats, to carry out further studies to assess the extent and condition of S. spinulosa reefs, and to develop appropriate measures of protection. Extending the boundary of the Southern Trench would have the added benefit of safeguarding additional features of conservation importance in the same zone, including kelp forests, submerged caves, and seven species that are considered Priority Marine Features in Scottish waters.